The Kappa Opioid Receptor: Candidate Pharmacotherapeutic Target for Multiple Sclerosis - Brian Reed; Surya Dutta (MDPI AG, 2023)
Multiple sclerosis (MS) afflicts millions of people worldwide. While multiple therapeutics have recently been developed and approved as treatment agents, they are not 100% effective. Recent developments investigating the endogenous opioid system involvement in MS has revealed that agonists of the kappa opioid receptor (KOR) have beneficial effects in both animal models of MS (and demyelinating disorders more generally) as well as in vitro models of remyelination. Several groups have contributed to this development. We summarize here the findings of these published studies, with comparisons of the effects and discussion of similarities and differences. The effects of KOR agonists involve both neuroimmunomodulation as well as remyelination, in different populations of cells. The compelling findings in MS model systems using KOR agonists strongly indicate that further investigations at both mechanistic and translational therapeutic levels are warranted.